Determinants of non-alcoholic fatty liver disease in young people: Maternal, neonatal, and adolescent factors. - Johannes Nairz; Alex Messner; Sophia J Kiechl; Bernhard Winder; Christoph Hochmayr; Alexander E Egger; Andrea Griesmacher; Ralf Geiger; Elke Griesmaier; Raimund Pechlaner; Michael Knoflach; Ursula Kiechl-Kohlendorfer; et al. (PLoS ONE, 2024)
Aim To assess the impact of maternal, neonatal, and adolescent factors on the development of non-alcoholic fatty liver disease (NAFLD) in a cohort of 14- to 19-year-old adolescents. Methods This study is part of the Early Vascular Ageing in the YOUth study, a single-center cross-sectional study conducted in western Austria. Maternal and neonatal factors were extracted from the mother-child booklet, adolescent factors were evaluated by a face-to-face interview, physical examination, and fasting blood analyses. Liver fat content was assessed by controlled attenuation parameter (CAP) using signals acquired by FibroScan® (Echosense, Paris, France). The association of maternal, neonatal, and adolescent factors with CAP values was analyzed using linear regression models. Results In total, 595 adolescents (27.2% male) aged 17.0 ± 1.3 years were included. 4.9% (n = 29) showed manifest NAFLD with CAP values above the 90th percentile. Male sex (p < 0.001), adolescent triglyceride levels (p = 0.021), Homeostatic Model Assessment for Insulin Resistance index and BMI z-score (p < 0.001, each) showed a significant association with liver fat content in the multivariable analysis. Maternal pre-pregnancy BMI was associated with CAP values after adjustment for sex, age, and birth weight for gestational age (p < 0.001), but this association was predominantly mediated by adolescent BMI (indirect effect b = 1.18, 95% CI [0.69, 1.77]). Conclusion Components of the metabolic syndrome were the most important predictors of adolescent liver fat content. Therefore, prevention of NAFLD should focus on lifestyle modification in childhood and adolescence.